2016
DOI: 10.1007/s00059-016-4469-6
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic cardiomyopathy

Abstract: The individual amount of alcohol consumed acutely or chronically decides on harm or benefit to a person’s health. Available data suggest that one to two drinks in men and one drink in women will benefit the cardiovascular system over time, one drink being 17.6 ml 100 % alcohol. Moderate drinking can reduce the incidence and mortality of coronary artery disease, heart failure, diabetes, ischemic and hemorrhagic stroke. More than this amount can lead to alcoholic cardiomyopathy, which is defined as alcohol toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
25

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(64 citation statements)
references
References 110 publications
0
39
0
25
Order By: Relevance
“…The most likely mechanism is that alcohol causes myocardial damage due to direct toxic and dosedependent effects of alcohol and its first metabolite acetaldehyde on the myocardium [5]. Furthermore, alcohol consumption may affect the heart via blood pressure elevation [23], since previous studies showed that heavy alcohol consumption was associated with higher blood pressure [24]. However, adjustment for antihypertensive medication use and SBP did not change the results.…”
Section: Discussionmentioning
confidence: 87%
“…The most likely mechanism is that alcohol causes myocardial damage due to direct toxic and dosedependent effects of alcohol and its first metabolite acetaldehyde on the myocardium [5]. Furthermore, alcohol consumption may affect the heart via blood pressure elevation [23], since previous studies showed that heavy alcohol consumption was associated with higher blood pressure [24]. However, adjustment for antihypertensive medication use and SBP did not change the results.…”
Section: Discussionmentioning
confidence: 87%
“…Many factors have been associated with the development of hypertension, such as an elevated body mass index, occupation, socioeconomic status, tobacco use, abdominal obesity, physical activity, and alcohol consumption, among others [5,48,51]. Many studies have reported a positive, dose-dependent association between alcohol intake and hypertension, showing the J-shaped curve also described for overall cardiovascular effects [5,16,19,22,[52][53][54][55][56]. Excessive alcohol consumption accounts for about 16% of cases of hypertension worldwide [5,57].…”
Section: Hypertensionmentioning
confidence: 99%
“…This issue also holds true for alcoholic cardiomyopathy [8]. In these patients, alcohol consumption of more than 40 g/day in men and more than 20 g/day in women for more than 5 years is the somewhat arbitrary diagnostic determinant for the label of alcoholic cardiomyopathy.…”
Section: Special Considerations For Complex Diagnosesmentioning
confidence: 99%